2001
DOI: 10.1002/1097-0142(20010615)91:12<2230::aid-cncr1253>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic magnetic resonance imaging of regional contrast access as an additional prognostic factor in pediatric osteosarcoma

Abstract: After careful planning, a postgraduate Diploma in Surgical Anatomy was launched in 2009. This report describes the structure of the program, the challenges encountered in implementing and running the course, and results of evaluations. The qualification is targeted at junior doctors intending to become surgeons or radiologists and aims to equip them with a sound understanding of regional anatomy relevant to common diagnostic and therapeutic procedures, together with an understanding of common/important anatomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 41 publications
(43 reference statements)
1
21
0
1
Order By: Relevance
“…MRI has no associated radiation exposure. Preliminary use of dynamic contrast-enhanced MRI is promising in assessing tumor response to therapy, but not all parts of the world have access to this technique and it presents unique challenges related to standardization of image acquisition, processing, and analysis [26]. …”
Section: Discussionmentioning
confidence: 99%
“…MRI has no associated radiation exposure. Preliminary use of dynamic contrast-enhanced MRI is promising in assessing tumor response to therapy, but not all parts of the world have access to this technique and it presents unique challenges related to standardization of image acquisition, processing, and analysis [26]. …”
Section: Discussionmentioning
confidence: 99%
“…In some cases, MR may redirect clinical management by distinguishing between malignant (Figure 3) and non-malignant (Figure 4_) disease. Dynamic enhanced MR techniques obtained at the time of diagnosis provide baseline information for following tumor response to therapy 95-97 (Figure 5). Thus far, a prognostic role for such techniques based upon findings at the time of diagnosis has not been established 84 .…”
Section: The Role Of Imagingmentioning
confidence: 99%
“…It serves as a surrogate variable for assessing drug delivery 67;95-97 but is not currently available for routine clinical use. This technique is an additional prognostic factor predictive of disease-free survival in patients receiving chemotherapy for osteosarcoma (p=0.035) 95;97 . A higher initial regional access of contrast was associated with greater disease-free survival 96 .…”
Section: Imaging Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In cancers other than breast cancer, it has been shown that dynamic contrast‐enhanced MR imaging (CE‐MRI) can contribute not only to establish the diagnosis, but also to identify patients with a poorer prognosis. Pharmacokinetic dynamic MR imaging was found to be a predictor of disease‐free survival in pediatric osteosarcoma (15). It has also been shown that MR imaging is able to assess tumor aggressiveness and offers information on the risk of local recurrence and on prediction of treatment success in cervical cancer (9, 12).…”
mentioning
confidence: 99%